Iran’s great scientific divergence: The Middle-Income trap and the Political Economy of Science Policy - Ehsan Roohi (PLoS ONE, 2026)
This study examines how the 1979 Iranian Revolution altered Iran’s long-term scientific development using publication and citation data for 1960–2024. Combining longitudinal scientometric analysis with counterfactual modeling, we identify a major structural break in Iran’s research trajectory after 1979. Iran experienced a substantial post-2000 recovery in publication volume , but this recovery was accompanied by a persistent quality gap, with Field-Weighted Citation Impact (FWCI) and top-cited-paper shares remaining below those of several comparator systems. To assess the long-run opportunity cost of the disruption, we use two complementary counterfactual strategies: a comparison-based Synthetic Control Method (SCM) and a set of developmental-growth proxy scenarios. Across specifications, the qualitative conclusion is stable: the post-1979 interruption is associated with a durable loss of scientific compounding capacity. At the same time, the quantitative magnitude of the cumulative shortfall is sensitive to counterfactual specification, indicating that no single benchmark should be treated as a definitive historical forecast. We therefore interpret the SCM results as comparison-based benchmarks and the developmental-growth proxies as illustrative upper- and mid-range scenarios rather than literal one-to-one counterfactuals. We interpret these findings through the lens of the Middle-Income Trap (MIT) and the political economy of the Rentier State . We argue that Iran’s post-revolutionary science policy contributed to a quantity–quality paradox in which expansion in scientific output was not matched by comparable gains in global scientific influence, while also recognizing that observed citation-impact measures are shaped by international collaboration constraints and bibliometric coverage limitations. The findings highlight the long-run developmental cost of political disruption while emphasizing that sustained scientific catch-up depends not only on output growth, but also on institutional continuity, international integration, and incentive structures that reward impact rather than volume alone.